THE STUDENTS’ ERROR IN PRONOUNCING ENGLISH CONSONANTS SOUNDS AT SMP 1 MUARO JAMBI - Ridwan, Adang (La Ogi : English Language Journal, 2024)
The aim of this study was to investigate students’ error in pronouncing English consonants sounds at eight grade students of SMP 1 Muaro Jambi. This is qualitative research, the research employing pronunciation test and interviews to collect data and data analysis in this research was descriptive analysis. The result of the study showed that there are four kinds of students’ error in pronouncing English consonants sounds at eight grade students of SMP 1 Muaro Jambi in the academic year of 2023/2024, they are omission is caused the incomplete application of rule, Addition is caused by the ignorance of rule restriction, Misformation is caused by the overgeneralization and Misordering is caused by the false concept hypothesized